Medicinal Plants Derived Nutraceuticals : A Re-Emerging Health Aid - NEHA PANDEY; RAM PRASAD MEENA; SANJAY KUMAR RAI; SHASHI PANDEY-RAI (International Journal of Pharma and Bio Sciences, 2011)
Nutritional therapy and phyto-therapy have emerged as new concepts of health aid in recent years. Strong recommendations for consumption of nutraceuticals from plant origin have become progressively popular to improve health, and to prevent and treat diseases. Nutraceuticals are "naturally derived bioactive compounds that are found in foods, dietary supplements and herbal products, and have health promoting, disease preventing and medicinal properties." Plant derived Nutraceuticals/functional foods have received considerable attention because of their presumed safety and potential nutritional and therapeutic effects. Some popular phyto-nutraceuticals include glucosamine from ginseng, Omega-3 fatty acids from linseed, Epigallocatechin gallate from green tea, lycopene form tomato etc. Majority of the nutraceuticals are claimed to possess multiple therapeutic benefits though substantial evidence is lacking for the benefits as well as unwanted effects. With these trends, improvement of the dietary nutritional values of fruits, vegetables and other crops or enhancement of the bioactive components in folk herbals have become the targets of blooming plant biotechnology industry. The present review has been devoted towards better understanding of the phyto-nutraceuticals from different medicinal plants based on their disease specific indications.